2013
DOI: 10.1111/tesg.12053
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital and Local Socio‐economic Development: The Case of Czech Peripheries

Abstract: The paper focuses on the relationship between social capital and local socio-economic development in the case of Czech peripheries. First, based on individual-level survey data, it examines relationships among various indicators of social capital encompassing three common dimensions: social networks, trust and civic norms and values. The results (correlations) confirm the existence of statistically significant and positive relationships. Second, the paper explores regional differences in social capital in typo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 59 publications
1
21
0
4
Order By: Relevance
“…Yet, researchers have also argued that there can be 'too much of a good thing' with high levels of bonding social capital detrimental to community/regional development and economic growth (Eklinder-Frick, Eriksson, & Hallén, 2012;Malecki, 2011;Pileček, Chromý, & Jančák, 2013;Woodhouse, 2006). This is consistent with findings presented by Eklinder-Frick et al (2012;2014) who found that high levels relational capital (trust) inhibited engagement with bridging ties and thereby decreased opportunities for business development and growth.…”
Section: Social Capital In Farming and Regional Developmentsupporting
confidence: 80%
“…Yet, researchers have also argued that there can be 'too much of a good thing' with high levels of bonding social capital detrimental to community/regional development and economic growth (Eklinder-Frick, Eriksson, & Hallén, 2012;Malecki, 2011;Pileček, Chromý, & Jančák, 2013;Woodhouse, 2006). This is consistent with findings presented by Eklinder-Frick et al (2012;2014) who found that high levels relational capital (trust) inhibited engagement with bridging ties and thereby decreased opportunities for business development and growth.…”
Section: Social Capital In Farming and Regional Developmentsupporting
confidence: 80%
“…Při bližším pohledu je totiž patrné, že jádra, ale ani periferie netvoří homogenní území a vznikání i zanikání periferií je komplikovaným multidimenzionálním procesem, v němž kromě faktorů ekonomické povahy hrají důležitou roli i sociokulturní aspekty, diskurzivní praktiky a různé formální i neformální instituce. Řada mimoekonomických faktorů, které ovlivňují situaci v periferním území, byla studována i v českém prostředí [Novotná 2005], a to zejména faktory kulturní povahy [Chromý, Skála 2010] a sociální kapitál [Majerová, Kostelecký, Sýkora 2011;Pileček, Chromý, Jančák 2013]. Výsledky výzkumů sociokulturních faktorů periferizace ukazují, že různá periferní území se od sebe mohou odlišovat z hlediska míry aktivity obyvatel a potenciálu pro endogenní rozvoj.…”
Section: Polarizační Teorieunclassified
“…We believe that the continuity of the settlement and its population could play a very important role. Together with Pileček et al (2013), we see social capital as an instrument for the activation of endogenous development in communities especially in peripheral regions. In contrast to human capital, which is given by qualification of local people, social capital is based on the long-term social stability.…”
Section: Chances and Challenges Of Remote Peripheral Micro-regions: Amentioning
confidence: 99%